Nano-Resveratrol: A Promising Candidate for the Treatment of Renal Toxicity Induced by Doxorubicin in Rats Through Modulation of Beclin-1 and mTOR - Alhusaini, Ahlam M.; Fadda, Laila M.; Alanazi, Abeer M.; Sarawi, Wedad S.; Alomar, Hatun A.; Ali, Hanaa M.; Hasan, Iman H.; Ali, Rehab Ahmed (Frontiers in Pharmacology, 2022)
Background: Although doxorubicin (DXR) is one of the most used anticancer drugs, it can cause life-threatening renal damage. There has been no effective treatment for DXR-induced renal damage until now. Aim: This work aims at examining the potential impact of nano-resveratrol (N-Resv), native resveratrol (Resv), and their combination with carvedilol (Card) against DXR-induced renal toxicity in rats and to investigate the mechanisms through which these antioxidants act to ameliorate DXR nephrotoxicity. Method: DXR was administered to rats (2 mg/kg, i.p.) twice weekly over 5 weeks. The antioxidants in question were taken 1 week before the DXR dose for 6 weeks. Results: DXR exhibited an elevation in serum urea, creatinine, renal lipid peroxide levels, endoglin expression, kidney injury molecule-1 (KIM-1), and beclin-1. On the other hand, renal podocin and mTOR expression and GSH levels were declined. In addition, DNA fragmentation was markedly increased in the DXR-administered group. Treatment with either Resv or N-Resv alone or in combination with Card ameliorated the previously measured parameters. Conclusion: N-Resv showed superior effectiveness relative to Resv in most of the measured parameters. Histopathological examination revealed amelioration of renal structural and cellular changes after DXR by Card and N-Resv, thus validating the previous biochemical and molecular results.